A preliminary study of contrast-enhanced ultrasound (CEUS) and cytokine expression analysis (CEA) as early predictors for the outcome of tibial non-union therapy - Haubruck, Patrick; Heller, Raban; Tanner, Michael Christopher; Daniel, Volker; Schmidmaier, Gerhard; Bolourchi, Farhoud; Moghaddam-Alvandi, Arash; Fischer, Christian (Diagnostics, 2018)
The current study investigates if contrast-enhanced ultrasound (CEUS) or cytokine expression analysis (CEA) evaluating vascularization are capable of predicting the outcome of non-union therapy. Patients with tibial non-unions were surgically treated and participated in our follow-up program including perioperative collection of blood as well as CEUS analysis. Two groups were formed: Responders in group 1 (G1, N = 8) and Non-Responders in group 2 (G2, N = 5). Serum cytokine expression and local microperfusion were compared and correlated to the radiologic outcome. Evaluation of TNF-α expression revealed significantly lower values prior to first surgery in G1 (G1: 9.66 ± 0.96 pg/mL versus G2: 12.63 ± 1.2 pg/mL; p = 0.045); whereas after treatment both CEA and CEUS indicated a higher potential for angiogenesis in Responders. Logistic regression modelling revealed the highest predictive power regarding eventual osseous consolidation for the combination of both CEUS and serum CEA. The results provide first evidence regarding a link between changes in the serum expression of distinct pro-angiogenic cytokines and alterations in the local microperfusion assessed via both non-invasive and radiation-free diagnostic modalities. In addition, a combination of CEUS and CEA is a promising novel tool in early prediction of the outcome of non-union therapy.